Arthroscopic Dorsal Capsulo-Ligamentous Repair in the Treatment of Chronic Scapho-Lunate Ligament Tears - Wahegaonkar, Abhijeet L.; Mathoulin, Christophe L. (Journal of Wrist Surgery, 2013)
Introduction Scapholunate ligament injuries usually result due to a fall on the outstretched hand leading to scapholunate instability. The natural history of untreated scapholunate instability remains controversial and usually results in late arthritic changes- the so-called “SLAC” wrist. The advent of wrist arthroscopy helps in early diagnosis and treatment of these serious injuries. In selected cases with reducible scapholunate instability (Garcia-Elias stages 2, 3 and 4) we propose a new “all arthroscopic dorsal capsulo- ligamentous repair” with the added advantage of early rehabilitation and prevention of post-operative stiffness.Material and Methods We report the results of our series of 57 consecutive patients suffering from chronic wrist pain refractory to conservative measures. All patients underwent a thorough clinical examination in addition to a standard set of radiographs and MRI exam; and they were treated by an all-arthroscopic dorsal capsulo-ligamentous repair under loco-regional anesthesia on an ambulatory basis. All patients were available for follow-up at regular intervals during the post-operative period. At follow-up, the wrist ROM in all directions, the grip strength, DASH questionnaire and pain relief based on the VAS were recorded for both- the operated and contra-lateral sides.Results There were 34 males & 23 females with a mean age of 38.72 ± 11.33 years (range 17–63 years). The dominant side was involved in 52 cases. The mean time since injury was 9.42 ± 6.33 months (range 3–24 months) and the mean follow-up was 30.74 ± 7.05 months (range 18–43 months). The mean range of motion improved in all directions. The mean difference between the post- and pre-operative extension was 14.03° (SEM = 1.27°; p < 0.001); while the mean difference between the post-and pre-operative flexion was 11.14° (SEM = 1.3°; p < 0.0001) with flexion and radial deviation reaching 84.3% and 95.72% respectively of the unaffected wrist. The mean difference for the VAS score was -5.46 (SEM = 0.19; p < 0.0001). The mean post-operative grip strength of the affected side was 38.42 ± 10.27 kg (range 20–60 kg) as compared with mean pre-operative grip strength of 24.07 ± 10.51 kg (range 8–40 kg) (p < 0.0001). The mean post-operative grip strength of the operated side was 93.4% of the unaffected side. The DISI was corrected in all cases on post-operative radiographs. The mean difference between the post-and pre-operative SL angles was −8.95° (SEM = 1.28°; p < 0.0001). The mean post-operative DASH score was 8.3 ± 7.82 as compared with mean pre-operative DASH score of 46.04 ± 16.57 (p < 0.0001). There was a negative co-relation between the overall DASH score and the post-operative correction of the DISI deformity with a lower DASH score associated with increasing SL angles.Discussion The dorsal portion of the scapholunate ligament is critical for the stability scapholunate articulation, largely due to its attachment to the dorsal capsule. We have recently conducted a multi-centric anatomical study with international collaboration demonstrating the critical importance of this dorsal scapholunate complex. The all arthroscopic capsulo-ligamentous repair technique provides reliable results in addition to avoiding postoperative stiffness. The overall results at a mean follow-up period of more than 2 years in our series of young, active patients appear to be encouraging.
Keywords: scapholunate ligament; chronic scapholunate injury; dorsal capsuloplasty; wrist arthroscopy